WELL BORE STABILITY MODEL BASED ON ITERATIVE COUPLING METHOD FOR WATER ALTERNATING GAS (WAG) INJECTION - BATHAEE, MAHMOOD (2016)
The water alternating gas injection is increasingly applied globally as the effective Enhanced Oil Recovery (EOR) method in oil wells. Fluid injection with high pressure or low temperature could lead to wellbore fracturing. The rock stress around the well bore is a function of the wellbore fluid flow and it should be determined to avoid the wellbore failure. The purpose of this study is to propose an iterative coupling method to ensure well bore stability for the WAG injection. The effective parameters such as pressures, temperature, saturations and stresses are obtained for the multi phase flow condition using mathematical modeling. In this study, finite difference method is used to calculate pressure, temperature and saturations; and finite volume method is applied to evaluate stresses. Iterative coupling method is used to improve the accuracy of the results. The mechanical properties of rock such as Poisson's ratio and Young modulus will be changed after saturation alteration.